Phosphate Starvation by Energy Metabolism Disturbance in Candida albicansvip1Δ/Δ Induces Lipid Droplet Accumulation and Cell Membrane Damage - Xueling Peng; Congcong Ma; Yuxin Feng; Biao Zhang; Mengsen Zhu; Tianyu Ma; Qilin Yu; Mingchun Li (Molecules, 2022)
Phosphorus in the form of phosphate (Pi) is an essential element for metabolic processes, including lipid metabolism. In yeast, the inositol polyphosphate kinase vip1 mediated synthesis of inositol heptakisphosphate (IP7) regulates the phosphate-responsive (PHO) signaling pathway, which plays an important role in response to Pi stress. The role of vip1 in Pi stress and lipid metabolism of Candida albicans has not yet been studied. We found that when vip1Δ/Δ was grown in glucose medium, if Pi was supplemented in the medium or mitochondrial Pi transporter was overexpressed in the strain, the lipid droplet (LD) content was reduced and membrane damage was alleviated. However, further studies showed that neither the addition of Pi nor the overexpression of the Pi transporter affected the energy balance of vip1Δ/Δ. In addition, the LD content of vip1Δ/Δ grown in Pi limitation medium PNMC was lower than that grown in SC, and the metabolic activity of vip1Δ/Δ grown in PNMC was also lower than that grown in SC medium. This suggests that the increase in Pi demand by a high energy metabolic rate is the cause of LD accumulation in vip1Δ/Δ. In addition, in the vip1Δ/Δ strains, the core transcription factor PHO4 in the PHO pathway was transported to the vacuole and degraded, which reduced the pathway activity. However, this does not mean that knocking out vip1 completely blocks the activation of the PHO pathway, because the LD content of vip1Δ/Δ grown in the medium with β-glycerol phosphate as the Pi source was significantly reduced. In summary, the increased Pi demand and the decreased PHO pathway activity in vip1Δ/Δ ultimately lead to LD accumulation and cell membrane damage.